Innovative Pedagogy and Design-Based Research on Flipped Learning in Higher Education - Zhao, Li; He, Wei; Su, Yu-Sheng (Frontiers in Psychology, 2021)
In order for higher education to provide students with up-to-date knowledge and relevant skillsets for their continued learning, it needs to keep pace with innovative pedagogy and cognitive sciences to ensure inclusive and equitable quality education for all. An adequate implementation of flipped learning, which can offer undergraduates education that is appropriate in a knowledge-based society, requires moving from traditional educational models to innovative pedagogy integrated with a playful learning environment (PLE) supported by Information and Communications Technologies (ICTs). In this paper, based on the design-based research, a task-driven instructional approach in the flipped classroom (TDIAFC) was designed and implemented for both of two groups of participants in an undergraduate hands-on making course in a PLE. One group consisting of 81 students as the experimental group (EG) received flipped learning instruction, and another group of 79 students as the control group (CG) received lecture-centered instruction. The EG students experienced a three-round study, with results from the first round informing the customized design of the second round and the second round informing the third round. The experimental results demonstrated that students in the EG got higher scores of summative tests and final scores than those in the CG. In particular, students’ learning performance in three domains (i.e., cognitive, affective, and psychomotor) differ significantly between the two groups.